Efficacy of PSMA ligand PET-based radiotherapy for recurrent prostate cancer after radical prostatectomy and salvage radiotherapy - Oehus, Ann-Kathrin; Kroeze, Stephanie G. C.; Schmidt-Hegemann, Nina-Sophie; Vogel, Marco M. E.; Kirste, Simon; Becker, Jessica; Burger, Irene A.; Derlin, Thorsten; Bartenstein, Peter; Eiber, Matthias; Mix, Michael; La Fougere, Christian; et al. (BMC Cancer, 2020)
Background: A substantial number of patients will develop further biochemical progression after radical prostatectomy (RP) and salvage radiotherapy (sRT). Recently published data using prostate-specific membrane antigen ligand positron emission tomography (PSMA - PET) for re-staging suggest that those recurrences are often located outside the prostate fossa and most of the patients have a limited number of metastases, making them amenable to metastasis-directed treatment (MDT). Methods: We analyzed 78 patients with biochemical progression after RP and sRT from a retrospective European multicenter database and assessed the biochemical recurrence-free survival (bRFS; PSA < nadir + 0.2 ng/ml or no PSA decline) as well as the androgen deprivation therapy- free survival (ADT-FS) using Kaplan-Meier curves. Log-rank test and multivariate analysis was performed to determine influencing factors. Results: A total of 185 PSMA - PET positive metastases were detected and all lesions were treated with radiotherapy (RT). Concurrent ADT was prescribed in 16.7% (13/78) of patients. The median PSA level before RT was 1.90 ng/mL (range, 0.1-22.1) and decreased statistically significantly to a median PSA nadir level of 0.26 ng/mL (range, 0.0-12.25; p < 0.001). The median PSA level of 0.88 ng/mL (range, 0.0-25.8) at the last follow-up was also statistically significantly lower (p = 0.008) than the median PSA level of 1.9 ng/mL (range, 0.1-22.1) before RT. The median bRFS was 17.0 months (95% CI, 14.2-19.8). After 12 months, 55.3% of patients were free of biochemical progression. Multivariate analyses showed that concurrent ADT was the most important independent factor for bRFS (p = 0.01). The median ADT-FS was not reached and exploratory statistical analyses estimated a median ADT-FS of 34.0 months (95% CI, 16.3-51.7). Multivariate analyses revealed no significant parameters for ADT-FS. Conclusions: RT as MDT based on PSMA - PET of all metastases of recurrent prostate cancer after RP and sRT represents a viable treatment option for well-informed and well-selected patients.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Oligometastases; Prostate cancer; PSMA; Radical prostatectomy; Radiotherapy; Recurrence